Corn starch/chitosan nanoparticles/thymol bio-nanocomposite films for potential food packaging applications - Othman, Siti Hajar; Othman, Nur Fitrah Liyana; Ahmad Shapi’i, Ruzanna; Ariffin, Siti Hajar; Md. Yunos, Khairul Faezah (Multidisciplinary Digital Publishing Institute, 2021)
This work aims to develop corn starch/chitosan nanoparticles/thymol (CS/CNP/Thy) bio-nanocomposite films as potential food packaging materials that can enhance the shelf life of food. CS/CNP/Thy bio-nanocomposite films were prepared by the addition of different concentrations of thymol (0, 1.5, 3.0, 4.5 w/w%) using a solvent casting method. The resulting films were characterized in terms of optical, mechanical, and water vapor permeability (WVP) properties. The addition of thymol was found to reduce the tensile strength (TS), elongation at break (EAB), and Young’s modulus (YM) of the films. Generally, the increment in the concentration of thymol did not significantly affect the TS, EAB, and YM values. The addition of 1.5 w/w% thymol increased the WVP of the films but the WVP reduced with the increase in thymol concentrations. CS/CNP/Thy-3% bio-nanocomposite films demonstrated the potential to lengthen the shelf life of cherry tomatoes packed with the films, whereby the cherry tomatoes exhibited no significant changes in firmness and the lowest weight loss. In addition, no mold growth was observed on the sliced cherry tomatoes that were in direct contact with the films during 7 days of storage, proving the promising application of the films as active food packaging materials.